Factors influencing intention to stay in a health-based voluntary activity - Ratna Dwi Wulandari, Nuzulul Kusuma Putri, Nyoman Anita Damayanti, R Darmawan Setijanto, Stefanus Supriyanto,; Akhsanu Ridlo, Ilham; Dwi Ratna Paramitha, Muhammad Ardian Cahya Laksana, Kartika Darma Handayani, (Opción, 2020)
This research aims to analyze the effect of task identity and social support on the intention of the volunteer to be continuously involved in the voluntary-based activities (GELIAT Program). This research was analytical observational research with a cross-sectional design. Samples were taken through simple random sampling. 102 volunteers from GELIAT Program asked to fill a questionnaire based on a Psychometric questionnaire. As a result, Task identity (P=0.042) and social support (P=0.036) significantly affected the intention of the volunteer to be continuously involved in voluntary activity. In conclusion, task identity and social support affecting volunteer intention to do voluntary activities.